Peran Komunikasi Public Relation (PR) dalam Meningkatkan Loyalitas Pelanggan dan Pertumbuhan Usaha pada Kedai Kopi Fikopi Premium Gayo - Fatimah Azzahra; Nosanda Nafisah Saki; Andini Indah Pratiwi; Nelly Armayanti (Prodi Pendidikan Administrasi Perkantoran UNIMED, 2025)
This study aims to analyze the role of Public Relations (PR) communication in increasing customer loyalty and business growth. Using a qualitative approach, the study was conducted through in-depth interviews with PR practitioners and business owners, as well as documentation analysis in the form of communication materials and company performance reports. The results indicate that effective PR communication through transparency, responsiveness, and message consistency can build customer trust, which impacts loyalty and business growth. In conclusion, PR plays a strategic role as a bridge between a company and its publics. This study recommends that companies continuously integrate PR strategies into customer relationship management. The implication is that a humanistic and values-based approach to PR communication can be a competitive differentiator amidst intense market competition.